Associação entre adesão à dieta mediterrânea e síndrome metabólica e seus componentes em participantes do ELSA-Brasil - Nascimento, Larissa de Carvalho (2019)
Metabolic syndrome (MS) is understood as a set of disorders related to cardiovascular risk. Its relevance has increased due to its high prevalence, besides being related to a high cost for the control of its components. Its etiology is complex, but it is linked to risk factors such as genetic predisposition, physical inactivity and diet with low nutritional value. For its prevention and treatment, pharmacological and non-pharmacological measures should be taken. In the non-pharmacological context, dietary intervention is essential, and the Mediterranean diet has been presented as an effective approach in the prevention and treatment of MS. The traditional Mediterranean diet is characteristic the countries of the Mediterranean basin, but is also widespread in other regions. Due to the variations suffered by this food pattern, different methodologies for evaluating its adherence were developed. However, Brazil is a country that does not have a proposal adapted to its population. The purpose of this cross-sectional study is to adapt the Mediterranean-Style Dietary Pattern Score (MSDPS), originally developed for Americans, to the Brazilian population, to apply it and investigate the association between dietary adherence and MS and its components in the ELSA population -Brazil (n = 15,105). The exclusion criteria were participants who changed their diet in the six months prior to the application of the food frequency questionnaire (FFQ), underwent bariatric surgery, were previously diagnosed with chronic diseases, presented implausible food intake and presented missing values for exposure and outcome variables. The diagnosis of MS was based on the NCEP ATPIII criteria, and the use of drugs associated with SM signs was also considered. The food consumption variables were collected by an FFQ developed and validated for the study population. After applying the exclusion criteria, the sample studied was 8,296 individuals (47.5% men and 52.5% women). The frequency of MS in the general sample was 35.7%. The most prevalent component was hyperglycemia (71.3% in the general sample and between the sexes - 81.1% in males and 62.4% in females). Adherence to the Mediterranean diet occurred in the range of 1.74 - 51.92%, being higher in females than in males (mean 23.4 vs. 22.74% p